Chemotaxonomic Study in the Heartwood of Javanese Teak: Analysis of Quinones and Other Related Components - Ganis Lukmandaru (Masyarakat Peneliti Kayu Indonesia, 2012)
Ethanol-benzene soluble extracts from the heartwood collected from 87 individual teak trees grown in the island of Java were analyzed using GC and GC-MS. The variations of quinones (tectoquinone, deoxylapachol, isodeoxylapachol, lapachol, tectol) and other components (palmitic acid, squalene, and two unknown compounds) were investigated for a chemotaxonomical study. There were wide variations in the contents of the constituents among individuals from three habitats, Purwakarta (plantation forest), Randublatung (plantation forest) and Gunungkidul (community forest) regions. Cluster and discriminant analysis results showed that teak trees can be classified into three clusters based on the composition of quinones and squalene. Cluster I was distinguished by relatively high amount of squalene and low amount of quinones. In contrast, high amount of tectoquinone and low amount of squalene was observed in cluster III. Further, comparatively high amount of naphtaquinones (lapachol, deoxylapachol and its isomer) and tectol was found in cluster II. Based on geographical distribution, Purwakarta, Randublatung, and Gunungkidul regions mostly produce cluster II, I, and III type individuals, respectively.